2019
DOI: 10.1097/coc.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Impact of a Cancer Diagnosis on Diabetes Management

Abstract: Objectives: Cancer patients with comorbid diabetes have a 50% increased risk of all-cause mortality compared with cancer patients without diabetes. Less attention to diabetes management (glucose control, medication adherence, and diabetes self-management behaviors) during active cancer treatment is hypothesized as an explanation for worse outcomes among diabetic cancer patients. The objective of this systematic review is to determine and quantify how a cancer diagnosis impacts diabetes management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Our study has important clinical implications. The impact of cancer diagnosis and treatment on diabetes management has drawn less attention, possibly because both clinicians and cancer patients may prioritise cancer over glycaemic control after a cancer diagnosis [ 60 ]. Based on current evidence, clinicians should continue to ensure glycaemic control in people with cancer and pre-existing diabetes, and it should be integral to clinical cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has important clinical implications. The impact of cancer diagnosis and treatment on diabetes management has drawn less attention, possibly because both clinicians and cancer patients may prioritise cancer over glycaemic control after a cancer diagnosis [ 60 ]. Based on current evidence, clinicians should continue to ensure glycaemic control in people with cancer and pre-existing diabetes, and it should be integral to clinical cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured topic guide was used to guide each patient interview. The topic guide was developed using insights from our group’s prior work [ 10 , 16 ], as well as discussions with clinical experts in endocrinology, primary care, and oncology. First, patients were asked to describe their overall experiences co-managing diabetes and breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work has shown that patients with cancer have difficulty finding time for diabetes management during cancer treatment, which they say demands their full attention [ 8 , 10 ]. We have also heard from oncologists that diabetes management is not their clinical priority or expertise [ 9 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though results are mixed, studies collectively indicate a deleterious effect of cancer and its treatment on diabetes management and control, which for many people is suboptimal even before diagnosis of cancer 13 14. Research shows that during cancer treatment many people with diabetes have reduced adherence to diabetes medications and self-care behaviours that contribute to glycaemic control (eg, blood glucose monitoring, eating healthily, exercising), and have poorer glycaemic control (eg, increased HbA1c levels, diabetes treatment escalations), than pre-cancer diagnosis 20 21. Studies have also noted that, following a cancer diagnosis, some people with diabetes undergo less diabetes-related screening aimed at mitigation of diabetic complications (eg, retinal screening, low-density lipoprotein tests) 22–24…”
Section: Introductionmentioning
confidence: 99%